Development of a multi-method analytical approach based on the combination of synchrotron radiation X-ray micro-analytical techniques and vibrational micro-spectroscopy methods to unveil the causes and mechanism of darkening of "fake-gilded" decorations in a Cimabue painting. Issue 1 (25th November 2021) - Monico, Letizia; Prati, Silvia; Sciutto, Giorgia; Catelli, Emilio; Romani, Aldo; Balbas, Diego Quintero; Li, Zelan; De Meyer, Steven; Nuyts, Gert; Janssens, Koen; Cotte, Marine; Garrevoet, Jan; et al.
Abstract : Synchrotron radiation X-ray micro-analytical techniques and vibrational micro-spectroscopy methods were used to establish the factors and mechanism of darkening of "fake-gilded" decorations in the Maestà by Cimabue and aged paint mock-ups. Abstract : Redox processes activated by environmental factors have been identified as the main cause of the chromatic alterations of a number of artists' pigments, including the yellow pigment orpiment (As2 S3 ). Although a general comprehension of the mechanisms has been provided through characterization of degradation compounds of As2 S3, experimental evidences to prove how other paint components and how different environmental agents influence the formation pathways of specific secondary compounds are still lacking. Thus, it becomes fundamental to develop a methodological strategy which enable achieving a discrimination among the causes affecting the chemical stability of more heterogenous As2 S3 -based paints and defining the mechanism through which the alteration establishes and evolves, with the ultimate goal of optimizing the preventive conservation measures of unique masterpieces. In this paper, we propose a comprehensive multi-material and multi-method approach based on the combination of synchrotron radiation X-ray micro-analytical techniques ( i.e., X-ray diffraction, X-ray fluorescence and X-ray absorption near edge structure spectroscopy at S K-/Ag L3 -/As K-edges) and vibrational micro-spectroscopy methods to unveil the causes and mechanism of darkening of "fake-gilded" decorations in tempera paintings, originally consisting of an unusual mixture of As2 S3 and metallic silver (Ag 0 ). Such degradation process is a not yet understood phenomenon threatening a series of Old Master paintings, including those by the Italian painters Cimabue and Pietro Lorenzetti. The high specificity, sensitivity and lateral resolution of the employed analytical methods allowed providing first-time evidence for the presence of black acanthite (α-Ag2 S), mimetite [Pb5 (AsO4 )3 Cl] and syngenite [K2 Ca(SO4 )2 ·H2 O] as degradation products of the "fake-gilded" decorations in the Maestà by Cimabue (Church of Santa Maria dei Servi, Bologna, Italy). Furthermore, the study of the painting combined with that of tempera paint mock-ups permitted to explore and define the environmental agents and internal factors causing the darkening, by proving that: (i) Ag 0 and moisture are key-factors for triggering the transformation of As2 S3 to α-Ag2 S and As-oxides; (ii) S 2- -ions arising from the degradation of As2 S3 are the main responsible for the formation of α-Ag2 S; (iii) light exposure strengthens the tendency of the paint components towards alteration. Based on our findings, we finally propose a degradation mechanism of As2 S3 /Ag 0 -based tempera paints.